THE INFLUENCE OF WORK ETHIC AND WORK ENVIRONMENT ON TEACHER PERFORMANCE WITH PROFESSIONAL COMPETENCE AS AN INTERVENING VARIABLE (Case Study at Al Mamsuriyyah Cikiwul Education Foundation) - Tian Bastian; Slamet Ahmadi (Sean Institute, 2023)
Teachers are the most important factor in education in general because for students teachers are often used as role models, even self-identity figures. Therefore, a teacher is required to perform his competence professionally accompanied by having a high work ethic and good performance supported by a harmonious work environment, this will affect the quality of education. Collaboration between teachers and students can